2017
DOI: 10.1177/1708538116684940
|View full text |Cite
|
Sign up to set email alerts
|

Endarterectomy for a symptomatic carotid web

Abstract: Background We report a symptomatic carotid web successfully treated with carotid endarterectomy. A healthy 43-year-old woman presented with acute-onset left-sided weakness. Carotid web was evident on computed tomography angiography as a focal filling defect in the right common carotid artery. This right common carotid artery web extended into the ICA created an eddy resulting in turbulent flow. Subsequent acute embolus formation led to embolization and acute stroke. Method Review of the literature was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 9 publications
(19 reference statements)
0
8
0
11
Order By: Relevance
“…Some have advocated the use of anticoagulation based on the fact that the mechanism of stroke is due to stasis-induced thrombosis, similar to that seen in strokes related to atrial fibrillation. Others have advocated for the use of endarterectomy to resect the web or carotid stenting [3, 7]. In a series of 25 patients with symptomatic carotid webs, Joux et al [3] performed endarterectomy in 7 cases with no cases of stroke recurrence or complications.…”
Section: Discussionmentioning
confidence: 99%
“…Some have advocated the use of anticoagulation based on the fact that the mechanism of stroke is due to stasis-induced thrombosis, similar to that seen in strokes related to atrial fibrillation. Others have advocated for the use of endarterectomy to resect the web or carotid stenting [3, 7]. In a series of 25 patients with symptomatic carotid webs, Joux et al [3] performed endarterectomy in 7 cases with no cases of stroke recurrence or complications.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, relevant studies on carotid webs were reported [ 1 5 ], which suggested that carotid webs are thin membrane structures protruding into the lumen; they are more common in the posterior or lateral posterior wall of the internal carotid bulb, and are approximately eight times more common in patients with stroke than in controls. Moreover, carotid webs are strongly associated with ischemic stroke [ 3 , 8 ], and they are one of the causes of cryptogenic stroke in young patients [ 1 , 4 , 10 , 15 ]. However, they are often missed [ 11 ] and could be an underappreciated risk factor for stroke [ 4 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ] described carotid webs using DUS in 1991 and 2004, respectively, and another case of carotid web by DUS was reported in 2015 [ 11 ]. While almost all diagnoses and reports on this disease were based on CTA or digital subtraction angiography, a study in 2017 using DUS reported on a carotid web with a short segment filling defect [ 15 ]. Thus, DUS could make an accurate diagnosis and may have the ability to diagnose carotid web.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Phair et al helped to distinguish carotid webs from FMD when they reported a patient presenting with an M1 occlusion whose CTA and MRI initially showed a filling defect at the right carotid artery bifurcation without a readily identifiable web. 16 Upon treatment with endarterectomy, a carotid web was seen, and histopathology showed smooth muscle with extensive myxoid degenerative changes, as opposed to the medial fibroplasia and loose collagen seen in FMD. 14 Although no studies compare endarterectomy vs stenting for treatment of a carotid web, we can extrapolate the data from carotid stenosis in which minimal risk is associated with carotid stenting using new stent technologies, 17,18 especially if performed after the first week from symptom presentation.…”
Section: Figure 3 Digital Subtraction Angiography Of Injections Of Tmentioning
confidence: 99%